Novel emulsifiers and stabilizers from apricot (Prunus armeniaca L.): their potential therapeutic targets and functional properties - Saadi, Sami; Saari, Nazamid; Ariffin, Abdul Azis; Mohd Ghazali, Hasanah; Abdul Hamid, Azizah; Abdulkarim, Sabo Mohammed; Anwar, Farooq; Nacer, Nor Elhouda (Elsevier, 2022)
Food emulsifiers and stabilizers such as starch, pectin, and cellulose that are derived from apricot (Prunus armeniaca L.) seed and seed residue are an emerging class of natural products, with potential industrial and medicinal benefits. Due to their important roles in colloid and copolymer, these derivative products are aimed to fulfill other biological functions like activation energy, signal transduction, and molecular repairing, in the living organisms. Their natural resistances and capability for copolymerization and as coating materials make them promising encapsulating agents for bioactive compounds. Apricot seeds are often discarded as agro-waste; however this under-utilized material can be explored as a valuable ingredient for development of various products of functional food and nutraceutical importance. In particular, they can be employed as ingredients in formulating dietetic, energetic foods and nutra-pharmaceuticals. Therefore, the main focus of this review is to evaluate and sum up the current state of the research on the therapeutic targets and functional properties of apricot derived components such as starch, pectin and cellulose towards enhancing the stability and resistance of formulated emulsions and by providing further bio ingredients destined in enriching dairy products.